2019
DOI: 10.1111/coa.13342
|View full text |Cite
|
Sign up to set email alerts
|

Changes of visualised Eustachian tube lengths by age and position: Radiologic study in sitting and supine positions using cone beam and conventional CT

Abstract: ObjectivesPatulous eustachian tube (ET) has been characterised by the visualisation of full‐length ET on computed tomography (CT) results. We wanted to investigate the changes of visualised ET lengths by age in supine and sitting positions.DesignRetrospective study.SettingTertiary care academic referral centre.ParticipantsOne hundred subjects who underwent cone beam CT (CBCT) in a sitting position and conventional CT in a supine position for non‐otitis‐related or dental complaints.Main outcome measuresVisualis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The ET lumen path length can be measured from cadaveric specimens, which were finely sectioned and 3D reconstructed to account for the curvature of the ET at the bony cartilaginous junction [ 6 ]. The measurement of ET lumen path length is not possible on CT scans unless under special circumstance such in patients with patulous ET [ 11 ], or with invasive injection of contrast media into the middle ear cleft [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ET lumen path length can be measured from cadaveric specimens, which were finely sectioned and 3D reconstructed to account for the curvature of the ET at the bony cartilaginous junction [ 6 ]. The measurement of ET lumen path length is not possible on CT scans unless under special circumstance such in patients with patulous ET [ 11 ], or with invasive injection of contrast media into the middle ear cleft [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased availability of high-resolution temporal bone computed tomography (CT) and the use of cone-beam CT, combined with the advent of multiplanar reconstruction (MPR) has made it possible for ETs to be measured on imaging studies [ 1 3 , 10 , 11 ]. A review of the literature revealed a range of methods in measuring ET angle and lengths, as summarised in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation